MEDIA PEMBELAJARAN E- LEARNING PADA MATA PELAJARAN BAHASA INGGRIS UNTUK SISWA KELAS VII SMP ADVENT MANOKWARI - Sinaga, Rinel; Maya Paembonan, Maya Paembonan; Sangka, Yuliana (DINAMIS, 2020)
The learning process is a teaching-learning process carried out by students and teachers in educational units. It takes a determination from various parties to achieve togetherness and the same vision in creating integrated integration in learning objectives. The Process of Teaching and Learning Activities (KBM) at Advent Manokwari Junior High School teachers only use printed books and do not utilize learning media, so the learning process becomes boring and makes students bored and learning is also less interesting. The purpose of this research is to design and develop E-Learning Learning Media in English Subjects for Class VII Students in order to facilitate teachers and students in learning and teaching activities at Manokwari Adventist Middle School. The design is done by making Learning Media that makes it easy for teacher teaching in the classroom. The design of this process includes Use Case Diagrams, Activity Diagrams, Sequance Diagrams and Class Diagrams that can explain the data flow and system characteristics that are processed to produce the desired information. The research results show the success rate of English Learning Media made is in accordance with the design made and also the learning media as a means of learning that is more interesting and interactive because it is more bring students closer to ICT for learning English. and can function as a means of gathering and discussion for students.